Overview and grouping of evaluation criteria for the effectiveness of mobile applications - A. I. Miftahova; E. I. Yangirov; E. I. Karaseva; A. I. Yangirov; E. Yu. Nikulina (Вестник Дагестанского государственного технического университета: Технические науки)
Objective. The study is conducted in order to identify the most valuable metrics for mobile application analytics and evaluate its effectiveness; consideration of the state and development trends of the mobile application market in the Russian Federation; determining priority areas for evaluating the effectiveness of mobile applications.Method. To achieve this goal, methods of analyzing promising scientific sources in the field of mobile application development are used, and development trends in this area in the Russian Federation are considered, taking into account political and social phenomena. This allows us to highlight the cause-and-effect relationships of the position of the direction of mobile application development in the market of the Russian Federation, as well as to identify promising evaluation criteria for the effectiveness of mobile applications. The information obtained allows us to consider the problems of developing mobile applications from a new point of view. To evaluate the effectiveness of performance indicators, methods of comparative analysis of mobile application data are used.Result. The results of the analysis of scientific sources are presented, the main evaluation criteria for the effectiveness of mobile applications are identified, their structuring is carried out, and the relationships between them are highlighted.Conclusion. The performance indicators considered in this study are applicable for predicting the competitiveness of mobile applications and assessing their attractiveness to users. It should be noted that in order to successfully measure the effectiveness of mobile applications, it is necessary to take into account the evaluation criteria that are important for a particular product in the aggregate. This makes it easier to identify aspects of mobile applications that need to be changed and modified.